A Response to the Essays - D'Costa, Gavin 1958- (2017)
Gavin D’Costa attempts to engage with his distinguished critics and acknowledges various shortcomings in his book. He also addresses a variety of questions related to the hermeneutics of interpreting the Council texts. While not neglecting post-Conciliar interpretative history, he stresses the importance of the debates about the texts and understanding their contextual, historical, linguistic evolution. D’Costa argues that theological movements, expert advisors and later reception history are all important but should not over-ride the basic intentions that can be established by the debates about versions of the text and the final voted Council text itself. D’Costa also discusses the unresolved tensions within Catholic theology regarding the validity of the Jewish covenant and the universal salvific role of Jesus Christ. This has major implications for mission to the Jewish people and D’Costa attends to a recent Vatican document on this matter. He touches more briefly on a host of other matters raised by his critics.